Enhancing Translation Pedagogy: Insights from a Needs Analysis of Course Materials - Asi, Natalina; Nugraha, Richard Ferry; Fauzan, Akhmad (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2025)
Abstract. This research investigates the material needs of third-year students enrolled in two classes of Translation courses at Universitas Palangka Raya, aiming to inform the development of a comprehensive translation module. A total of 108 students participated in the study, providing valuable insights through a structured questionnaire designed to assess their specific requirements for translation materials. A qualitative approach using structured questionnaires was used, allowing for both thematic analysis of open-ended responses and percentage-based summaries of closed-ended items. This enabled an in-depth understanding of the students’ perspectives and learning needs. The findings revealed that the majority of students felt the current materials were adequate, but highlighted the need for a more structured and accessible module. Specifically, students expressed a desire for materials that bridge the gap between theory and practice, including more examples, practical exercises, and structured guidance across different types of texts, such as academic, commercial, and literary works. The results underscore the importance of developing a tailored translation module that not only covers the theoretical aspects of translation but also provides ample opportunities for students to apply their knowledge in practice. This study provides a foundational basis for enhancing the Translation courses at Universitas Palangka Raya, ensuring that the curriculum aligns more closely with the actual needs of students.Keywords: : translation, module, learning materials, EFL students, need analysis